An exact block algorithm for no-idle RPQ problem - Pempera, Jaroslaw (Archives of Control Sciences, 2017)
Abstract In the work a single-machine scheduling problem is being considered, in which all tasks have a fixed availability (release) and delivery time. In the analyzed variant no-idle time is allowed on a machine. The purpose of optimization is to determine such order of tasks that minimizes the makespan, i.e. the time of execution of all the tasks. There is also a number of properties of the problem presented, in particular there are formulated block eliminating properties for no-idle constraint. There was an exact B&B algorithm based on the block properties proposed.